Apport de l’écologie du paysage dans un espace insulaire fortement anthropisé : exemple de la Martinique - Peguy Major (VertigO)
In a context of strong anthropogenic evolution of the landscape of Martinique, this article has for objective of to identify the relevant variables to describe the spatial structure, the dynamics and the organization of the landscape of Martinique. This work is of the ecology of the landscape, as multidisciplinary science, her proposes a very good approach of a methodology organizing the structure and the components of the landscape to highlight the causes and the consequences of the ecological processes. The method used for this study of the anthropogenic evolution of the landscape of Martinique was cards IGN of 1954, on 1996 and 2016. Two zones of studies were chosen to analyze and compare the transformation of the landscape under the action of the man. Two zones of studies were chosen to analyze and compare the effects of the anthropisation on the biodiversity. The results show that the landscape of Martinique underwent an important processing connected mainly to the disturbances of anthropological order and to the demographic pressure through the ages of precolonial period in today.